Editorial de la revista número 1 del año 2004 - Fustiñana, Carlos (Revista del Hospital Italiano de Buenos Aires, 2004)
Renewal is one of the main characteristics of dissemination organs, both in general outreach and in scientific publications. In this sense, the Editorial Board of the Hospital Italiano Journal is no exception. After nearly a decade at its helm, I step down as Director of the Journal, remaining a member of the Editorial Board.Leaving a role held for many years is difficult, particularly when it involves personal relationships. I must especially thank two people who accompanied me throughout this period: Norma Hernández and María del Rosario Revello (Charito), who have been irreplaceable collaborators. Together with them and other colleagues, we sustained the vision of maintaining editorial continuity despite the crises that affected all Argentinians. Although we barely achieved that goal, today, with the collaboration of the Hospital’s Medical Direction and the Department of Teaching and Research, the Editorial Board ensures the Journal’s continuity.Several milestones marked our tenure. We sought to reflect in the Journal activities spanning the entire Hospital, including significant topics such as ethics –remember the special issue dedicated to Dr. Diego Gracia’s lectures– and a series of notes on research and study design, published before evidence-based medicine became standard practice.A space was created to showcase scientific advances, many arising from the current Institute of Basic Sciences and Experimental Medicine, alongside a section dedicated to teaching updates. The inclusion of Care Guidelines deserves special mention, as they establish the Hospital’s standards for diagnosis and treatment.Another highlight was the publication of two Extraordinary Issues celebrating the 100th anniversary of the Gascón Site and the 150th anniversary of the Hospital, entrusted to us by Dr. Enrique Caruso and carried out with the support of Drs. Mario Sebastiani and Sung Ho Hyon, along with many other collaborators.Recognition is extended to all those who selflessly dedicate their time to make this publication possible. From its inception, the Journal was conceived as a platform to showcase the full scope of activities at Hospital Italiano, with scientific rigor endorsed by a review committee, navigating the challenges arising from the Institution’s diversity.This challenge remains, and I am confident that the response will exceed our expectations. Thank you to all who trusted us by submitting the fruits of their work.